Muscle activation in middle-distance athletes with compression stockings - Moreno-Pérez, D.; Marin, J. P.; López-Samanes, Á.; Cejuela-Anta, R.; Esteve-Lanao, J. (Sensors, 2020)
The aim of this study was to evaluate changes in electromyographic activity with the use of gradual compression stockings (GCSs) on middle-distance endurance athletes` performance, based on surface electromyography measurement techniques. Sixteen well-trained athletes were recruited (mean ± SD: age 33.4 ± 6.3 years, VO2max 63.7 ± 6.3 mL·kg-1·min-1, maximal aerobic speed 19.7 ± 1.5 km·h). The athletes were divided into two groups and were assigned in a randomized order to their respective groups according to their experience with the use of GCSs. Initially, a maximum oxygen consumption (VO2max) test was performed to standardize the athletes` running speeds for subsequent tests. Afterward, electromyographic activity, metabolic, and performance variables for each group were measured with surface electromyography. In addition, blood lactate concentration was measured, both with and without GCSs, during 10 min at 3% above VT2 (second ventilatory threshold), all of which were performed on the track. Next, surface electromyography activity was measured during a 1 km run at maximum speed. No significant changes were found in electromyography activity, metabolic and performance variables with GCSs use (p > 0.164) in any of the variables measured. Overall, there were no performance benefits when using compression garments against a control condition.